Parent and patient perspective of fatal and near-fatal asthma - McMurray, Ann; Cavers, Debbie (The University of Edinburgh, 2022)
INTRODUCTION: Asthma is one of the most common long term conditions, typically affecting 1 in 11 children and 1 in 12 adults within the UK. Although asthma attacks are common, near-fatal asthma attacks and asthma deaths are rare. Statistics are available worldwide for asthma deaths, but the true incidence of near-fatal asthma (NFA) is unknown as there is no current definition to use as a benchmark. Factors which contribute to near-fatal and fatal asthma attacks have been identified in literature and confidential enquires. To date, however, there are no known studies that have examined these attacks from the patient and parent/carer perspective. AIMS/OBJECTIVES OF THE PHD: The overarching aim of this study was to define NFA and identify potential modifiable behaviours to reduce the risk of NFA and an asthma-related death. This PhD study was sub-divided into two components: 1.A scoping review, an asthma guideline review and an eDelphi study to identify a consensus definition of NFA 2.Qualitative interviews to explore parents’ and young adults’ perspectives of fatal and near-fatal asthma. Component one aims were to: •Gain an international clinical consensus name and definition for a ‘critical asthma attack’ to enable the frequency of defined attacks to be measured, against which future interventions can be trialled to reduce these and asthma deaths. •Utilise the consensus name and definition to identify participants for the NFA qualitative study The aims for the scoping review and asthma guideline review were included as chapter aims. Component two aims were to: •Identify key time-critical experiences of those who have experienced NFA (or their parents), or parents of those whose child died of asthma, that may provide a window of opportunity to seek help. •Understand family circumstances and behaviours that may place children and young people at greater risk of asthma death/near fatal asthma. •To understand the long-term psychosocial consequences of NFA. • To use these findings to inform key stakeholders such as education, primary care, severe asthma registries and emergency service responses, in order to reduce the risks of fatal and near-fatal asthma and provide appropriate support for children and young people (CYP), young adults and their families. In order to achieve these aims, interviews were carried out to give the opportunity to parents of children and young adults who have experienced NFA attacks and bereaved parents of children who have suffered a fatal attack, to describe their experience. METHODS AND FINDINGS: The programme of work was sub-divided into two components. Component One included a scoping review, asthma guideline review and an eDelphi. The term ‘critical asthma attack’ was used within this component as the name for the attack was evolved. Scoping review and asthma guidelines review Following the methodology proposed by Arksey and O’Malley, with adaptations by Levac et al., and the Joanna Briggs Institute, a five stage scoping review was conducted to identify names, definitions, objective measurements, clinical features and parent/ perspective of a critical asthma attack, which could result in an asthma death. To supplement the findings of the scoping review, a review of asthma guidelines available worldwide was also conducted using the same research questions as the scoping review. Results from both reviews were used to inform the initial eDelphi questionnaire. eDelphi: I recruited an international expert panel to gain consensus for a clinical name and definition for a critical asthma attack. Overall, 104 participants from 25 countries completed all three rounds of the study. Participants worked across the fields of respiratory, critical care and emergency department medicine, caring for both adults and children. Near-fatal asthma was the agreed name for the event and was defined as, “A near-fatal asthma attack occurs in a person who is exhausted, with severe dyspnoea, unable to speak, with a silent chest. Respiratory arrest is considered imminent and invasive ventilation will likely be required. They will be responding poorly to emergency asthma therapies. This is associated with hypoxaemia, hypercarbia and a falling pH”. This definition was used to recruit participants to the near-fatal asthma studies. Parent and patient interviews: A total of 24 single, in-depth semi-structured interviews were conducted. Five young people and 12 parents, which included two couples, who had been affected by near-fatal asthma attacks and seven parents affected by asthma deaths participated. Interviews were recorded and transcribed verbatim. Interviews were analysed using thematic analysis from a modified constructivist grounded theory approach, assisted by NVivo pro version 11 to manage the data. Trusting your intuition, following an asthma plan and calling emergency services were identified as key time critical opportunities, which emerged within both the fatal and near fatal asthma interviews. When considering behaviours and circumstances the attitude of ‘it’s just asthma’ in conjunction with knowledge and awareness of asthma management and the impact of previous attacks, were identified in both studies. The long lasting social and psychological effects post NFA were identified as long-term consequence, with an impact on both the person who had experienced the attack and the wider family. DISCUSSION AND CONCLUSION: To the best of my knowledge this is the first time parents and young adults have had the opportunity to share their perspective of fatal and NFA attacks. The definition of near-fatal asthma, which has been agreed by international consensus, once published, could be used in future studies against which interventions could be measured. There were areas of current knowledge with regards to risk factors for a NFA attack or asthma death that could be enhanced. These included: a previous NFA attack; previous admission to hospital; heavy/ overuse of SABA; psychological impact and clinicians’ knowledge. The novel findings of this study that should be implemented into care and policy include: the power of intuition; the effect of hypoxaemia on decision making; the normalisation of asthma; and lack of awareness that asthma attacks can result in asthma death. These findings were mapped into the social-ecological model used as a framework for this study. This model considered individual, interpersonal, community, organisational and public policy factors and how important implementing change across multiple levels of the model at the same time are required to improve outcomes for children and young people affected by asthma. The findings from both studies could be applied to educational packages, emergency service algorithms and severe asthma registries, with an aim to reduce asthma attacks and asthma deaths.